1993
DOI: 10.2466/pms.1993.77.2.535
|View full text |Cite
|
Sign up to set email alerts
|

Young Children's Divergent Movement Ability

Abstract: To examine the relations of age, gender, movement experience, and gross motor development to young children's scores on divergent movement (i.e., ability to perform and modify fundamental movement patterns), 40 boys and girls ages 4, 6, and 8 years were tested. Ability to make divergent movements was evaluated by having subjects perform 3 different fundamental movement tasks. Movement experience was assessed by asking parents to complete a questionnaire. Ulrich's Test of Gross Motor Development was used to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
19

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 10 publications
3
39
0
19
Order By: Relevance
“…Similarly, the marked increase between Levels 1 and 2 is in keeping with the reports of significant advances between ages 7 and 8 years (Torrance, 1981;Cleland & Gallahue, 1993). However, while this pattern of between-level differences was evident for locomotor fluency and manipulative fluency (though the differences were only statistically significant for the latter, which was on average slightly lower in Level 3 than Level 2), symbolic fluency exhibited the contrary pattern, the significant difference between Levels 1 and 3 being due largely to an increase between Levels 2 and 3 that, while not in itself statistically significant, was twice as large as the increase between Levels 1 and 2.The absence of any increase in manipulative fluency between Levels 2 and 3 may possibly be linked to the progress of motor coordination.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Similarly, the marked increase between Levels 1 and 2 is in keeping with the reports of significant advances between ages 7 and 8 years (Torrance, 1981;Cleland & Gallahue, 1993). However, while this pattern of between-level differences was evident for locomotor fluency and manipulative fluency (though the differences were only statistically significant for the latter, which was on average slightly lower in Level 3 than Level 2), symbolic fluency exhibited the contrary pattern, the significant difference between Levels 1 and 3 being due largely to an increase between Levels 2 and 3 that, while not in itself statistically significant, was twice as large as the increase between Levels 1 and 2.The absence of any increase in manipulative fluency between Levels 2 and 3 may possibly be linked to the progress of motor coordination.…”
supporting
confidence: 68%
“…One of the main difficulties in the evaluation of motor flexibility, the establishment of an appropriate taxonomy of movement categories, was tackled by these authors by defining a category change as a change in one of the basic parameters defining the structure of a motor skill (location, rhythm, spatial relationships, force, etc.). In their study of 40 children aged 4-8 years, they observed significant increments in both fluency and flexibility (Cleland & Gallahue, 1993). Zachopoulou, Makri and Pollatou (2009) recently reported the existence of close correlation between TCAM and DMA scores.…”
Section: Introductionmentioning
confidence: 99%
“…The more opportunities given to children for practice, the more they develop their movement repertoire and refine the fundamental motor skills (Cleland and Gallahue 1993). Training intervention is considered to be the most important factor which may influence motor development (Roth and Winter 1994).…”
Section: Intervention Movement Programsmentioning
confidence: 99%
“…The instrument was widely used to measure gross motor abilities that develop early in life (Cleland & Gallahue, 1993;Cooley et al, 1997;Goodway, Crowe, & Ward, 2003;Evaggelinou, Tsigilis, & Papa, 2002;Karabourniotis et al, 2002). There are two subtests of items, Locomotor and Object Control.…”
Section: Instrumentationmentioning
confidence: 99%